2021
DOI: 10.29040/jiei.v7i2.2534
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Profitabilitas Bank Syariah Indonesia dan Malaysia

Abstract: One of the benchmarks for state progress in banking which affects economic activity (Khasanah, 2016) . This study aims to determine the factors that influence profitability included CAR, BOPO, FDR, on ROA with NPF as a moderating variable for Indonesian and Malaysian Islamic banking listed in the Financial Services Authority (OJK) and Bank Negara Malaysia (BNM) for the 2014-2019 period. This type of quantitative research with secondary data is in the form of panel data. The sample includes 11 Indonesian Islami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
0
1
3
Order By: Relevance
“…The ratio of Operating Expenses to Operating Revenue Variable (bopo) BOPO has an effect on the profit-sharing provided by Islamic banks, in accordance with many previous studies. However, this is different from Mismiwati (2019) which found that Profit Distribution Management was not significantly affected by BOPO and findings of Astuti (2021) which state that BOPO has a positive effect but does not affect the profitability of Islamic banking in Indonesia and Malaysia.…”
Section: Return On Equity Variable (Roe)contrasting
confidence: 89%
See 1 more Smart Citation
“…The ratio of Operating Expenses to Operating Revenue Variable (bopo) BOPO has an effect on the profit-sharing provided by Islamic banks, in accordance with many previous studies. However, this is different from Mismiwati (2019) which found that Profit Distribution Management was not significantly affected by BOPO and findings of Astuti (2021) which state that BOPO has a positive effect but does not affect the profitability of Islamic banking in Indonesia and Malaysia.…”
Section: Return On Equity Variable (Roe)contrasting
confidence: 89%
“…FDR has an influence on the profit sharing of Islamic banking, in line with the findings of Vustany (2006), and contrary to the findings of Tugiantoro (2014) which state that FDR has no effect on profit sharing and findings of Astuti (2021) which state that FDR has a positive effect but does not affect the profitability of Islamic banking in Indonesia and Malaysia.…”
Section: Financing To Deposit Ratio Variable (Fdr)supporting
confidence: 59%
“…Berdasarkan tabel 1 menunjukkan bahwa Return On Asset (ROA) PT. BRI Syariah, Tbk selalu berada dibawah standar yang ditetapkan oleh Bank Indonesia (BI) yaitu diatas 1,215%) (Astuti & Kabib, 2021). Semakin besar ROA suatu bank, semakin besar pula tingkat keuntungan yang dicapai bank, dan semakin baik pula posisi bank dari segi penggunaan aset.…”
Section: Tahununclassified
“…The research instrument used secondary data processed from Bank BJB Syariah. The results of the research that have been conducted show that the simultaneous test shows that independent variable NPF and BOPO which has a significant effect on the ROA of Bank BJB Syariah (2014-2021. The partial test results on the NPF variable have a significant effect on ROA, while the BOPO variable has no significant effect on ROA.…”
mentioning
confidence: 92%
“…
This research was motivated by the acquisition of an unstable level of profitability of Bank BJB Syariah, which even experienced losses with a minus profitability. This study aims to analyze whether Non Performing Financing (NPF) and Operating Costs to Operating Income (BOPO) simultaneously affect the Profitability (ROA) of Bank BJB Syariah (2014-2021,as well as to analyze whether NPF and BOPO partially affect the ROA of Bank BJB Syariah (2014-2021, and to analyze which factor has the most effect on ROA. This study used a quantitative method and the sample in this study was the financial statements of Bank BJB Syariah (2014-2021 and sampling technique was purposive sampling method.
…”
mentioning
confidence: 99%